2021
DOI: 10.1177/23742895211010322
|View full text |Cite
|
Sign up to set email alerts
|

Women in Academic Pathology: Pathways to Department Chair

Abstract: The Association of Pathology Chairs, an organization of American and Canadian academic pathology departments, has a record percent of women department chairs in its ranks (31%), although still not representative of the percent of women pathology faculty (43%). These women chairs were surveyed to determine what had impeded and what had facilitated their academic advancement before becoming chairs. The 2 most frequently identified impediments to their career advancement were heavy clinical loads and the lack of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…Prior leadership experience was considered important in the career success of both interim and permanent female chairs of pathology. 2 Academic pathology departments typically offer many opportunities for leadership, and deans are likely to choose from among faculty members with leadership experience to serve as the interim chair. Although serving as an interim chair can have a negative impact on one's career, it can also be beneficial, including providing the added leadership experience needed for success in becoming a permanent chair.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Prior leadership experience was considered important in the career success of both interim and permanent female chairs of pathology. 2 Academic pathology departments typically offer many opportunities for leadership, and deans are likely to choose from among faculty members with leadership experience to serve as the interim chair. Although serving as an interim chair can have a negative impact on one's career, it can also be beneficial, including providing the added leadership experience needed for success in becoming a permanent chair.…”
Section: Discussionmentioning
confidence: 99%
“…In a previous publication about female chairs of pathology, we reported that females made up 31% of the total 166 Association of Pathology Chairs (APC) department chairs, although at that time females constituted 43% of faculty in academic departments of pathology. 2 In a survey of these female chairs administered in September 2020 to determine what facilitated or hampered their career advancement, we reported that previous leadership roles were important. 2 We also reported that of 18 interim chairs at that time, 65% were females.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This disparity is reflective of the general trend in surgery and pathology leadership nationally. 3,4 Furthermore, utilizing data from 2012 to 2014, Qiu et al 5 showed that diversity in academic dermatology faculty decreases significantly with increasing faculty rank. Our data mirror this sentiment by demonstrating a majority of women in assistant and associate PD positions, with a minority of women chairs.…”
Section: Dear Editorsmentioning
confidence: 99%
“…1 As noted by Lipscomb et al., 2020 data from the Association of Pathology Chairs (APC) demonstrate 31% women chairs within member departments, with the difference from AAMC data being explained by an additional 32 academic “affiliate” members (departments not in a medical school but that have pathology graduate medical education programs). 2 APC is committed to increasing diversity within pathology leadership, focusing primarily on race and gender. However, other attributes such as leadership background, primary pathology training, sub-specialty focus, and skill sets could also be considered within diversity as academic pathology departments vary greatly across the United States.…”
Section: Introductionmentioning
confidence: 99%